Flexible Management of Technology Adoption and Adaptation in Manufacturing Industry - Sethi, Amanpreet Singh (My University, 2009)
ABSTRACT The manufacturing sector has undergone major changes in last few decades. The pace of change in India increased when firms adopted and adapted new technologies since early 1990s. Links of flexibility issues to capability building in manufacturing firms have not been adequately addressed in enormous literature on technology adoption and adaptation (TAA). Broad objective of this research work was to analyze the technology adoption and adaptation processes used in Indian manufacturing companies and to develop a framework representing the linkages of TAA with capability building of these companies. Major issues taken up were to assess the TAA practices and policies, identify problems of and barriers to TAA, study flexible approaches in TAA for capability building, and develop a conceptual framework of flexible system for this. Literature was reviewed extensively for identifying specific factors affecting TAA, and capability building. The research has been carried out using flexible system methodology. The problem has been conceptualized as an S-A-P paradigm. A questionnaire having 1–4 Likert-type scale for all item measures was designed for survey. It was validated through peer review from academics and industry. Descriptive and empirical analyses of the data collected was done for finding status of TAA and present level of technological capabilities. Further, the associations between various independent constructs and outputs (technological capabilities, success due to adoption and adaptation of new technology and flexibility) were established using canonical correlation and multiple regression analysis. Association of TAA policies with capability building was established using correlation coefficient. Problems of bringing old and new technology together were explored, critical barriers in TAA identified, and action required for overcoming these barriers suggested. Survey was followed by four case studies on representative firms. (Maruti Suzuki India Ltd., Sona Koyo Steering Systems Ltd., Moserbaer India Limited, and Punjab Tractors Ltd.). Learning issues from survey and case studies were synthesized to develop a systematic implementation plan for effectively managing the different flexibilities in manufacturing organizations. For this, a qualitative modeling technique has been applied using OFM, OPM, AHP and FST. Four approaches for new TAA practices were developed: hard technology adoption, soft technology adoption, technology adaptation, and system adaptation approaches. A conceptual framework representing the linkages between TAA and technological capability building for a company was developed. Further, for building different types of technological capabilities, an order of implementing various strategies in Indian context was recommended. Conclusion: manufacturing companies must concentrate on the technology adaptations, followed by system adaptations, and then on hard technology adoptions for building their overall technological capabilities. A few suggestions for further research are given.
Ph.D.
Keywords: Technological Capabilities; Technology flexibility